2013
DOI: 10.1161/hypertensionaha.112.193250
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane Receptors in Smooth Muscle Promote Hypertension, Vascular Remodeling, and Sudden Death

Abstract: Abstract-The prostanoid thromboxane A 2 has been implicated to contribute to the pathogenesis of many cardiovascular diseases, including hypertension. To study the role of vascular thromboxane-prostanoid (TP) receptors in blood pressure regulation, we generated mice with cell-specific deletion of TP receptors in smooth muscle using Cre/Loxp technology. We crossed the KISM22α-Cre transgenic mouse line expressing Cre recombinase in smooth muscle cells with a mouse line bearing a conditional allele of the Tbxa2r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…miR-31 also achieves its angiogenic role by targeting the receptor of TBXA2. TBXA2, which is a prostanoid, has received great attention because of its involvement in platelet function and the pathogenesis of many cardiovascular diseases, including atherosclerosis and hypertension, 55,56 via interaction with its specific receptor TBXA2R, a G proteincoupled receptor on endothelial cells. 26 TBXA2R signaling is able to inhibit VEGF-induced endothelial cell differentiation and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-31 also achieves its angiogenic role by targeting the receptor of TBXA2. TBXA2, which is a prostanoid, has received great attention because of its involvement in platelet function and the pathogenesis of many cardiovascular diseases, including atherosclerosis and hypertension, 55,56 via interaction with its specific receptor TBXA2R, a G proteincoupled receptor on endothelial cells. 26 TBXA2R signaling is able to inhibit VEGF-induced endothelial cell differentiation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…TBXA2R in smooth muscle promotes angiotensin II-induced hypertension, vascular remodeling, and sudden death. 56 Recent experimental findings have indicated that synthetic TBXA2/prostaglandin receptor inhibitors seem to have potent antiplatelet activity with an antiatherosclerotic effect. Such activity has important implications especially when they are used to target clinical conditions associated with an increased production of prostanoids, such as CAD and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Using the mTmG dual-reporter mouse line, 12 we have previously demonstrated robust green fluorescent protein fluorescence in the media of the aorta and throughout glomerular afferent arterioles in KISm22a-Cre-mTmG mice, confirming robust expression of Cre-recombinase in large arteries and resistance vessels. 13 To document efficient elimination of AT 1A receptors, we measured levels for AT 1A receptor mRNA by real-time quantitiative RT-PCR. Segments of the aorta were isolated from SMKO and control mice.…”
Section: Generation Of Mice With Cell-specific Deletion Of At 1 Recepmentioning
confidence: 99%
“…22 It is broadly distributed throughout the body, with higher expression observed in the immune organs. 23 Thromboxane/TP has been implicated in allergic inflammation, 24 blood pressure regulation, 25 vascular remodeling, 26 and atherosclerosis. 27 TP receptor antagonists display multiple beneficial effects in cardiovascular diseases.…”
mentioning
confidence: 99%